An Educational Transformation Strategy to Mitigate the Effects of Unemployment During Indonesia's Demographic Bonus (2020-2030) - Syahputri, Arridhatul (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Unemployment in Indonesia is a non-conventional threat to human security, particularly within the economic sector. The threat of unemployment can even have a broader impact and become a threat in other sectors, such as social instability, politics, and state security. This threat is becoming an increasingly worrying issue when Indonesia enters the demographic bonus era, where there will be an explosion in the productive age groups (15–64 years), as can be seen from the addition of the workforce reaching 4 million people every year. This research examines the threat of unemployment in the demographic bonus era and deals with this threat through educational transformation policies. This research uses a qualitative descriptive method with data collection techniques through interviews and literature studies. The results of this research show that the threat of unemployment in the Indonesian demographic bonus era is quite significant, mainly because the quality of human resources in Indonesia is still relatively low. The strategy implemented is improving the quality of human resources for Indonesian workers through educational transformation and vocational training that can produce competent, creative, and skilled human resources who can meet the demands of the job market, and in addition to providing opportunities for individuals to become entrepreneurs.